PERAN KEPALA DUSUN DALAM DINAMIKA INTERAKSI SOSIAL DAN SOLIDARITAS MASYARAKAT DUSUN VI PATUMBAK - Nurjannah; Siti Ayu Saskia Nasution; Sri Wahyuni; Tiara Dwi Atika; Mutiara Hasanah; Sekar Rizkia (STKIP Subang, 2025)
This study aims to analyze the role of the hamlet head in the dynamics of social interaction and social solidarity within the community of Dusun VI Patumbak. As a local leader, the hamlet head plays a strategic role in shaping social relations, maintaining social harmony, and strengthening socio-cultural values within the community. This research employed a descriptive qualitative approach, with data collected through observation, in-depth interviews, and documentation. The head of Dusun VI Patumbak was selected as the key informant, while community members served as supporting informants. The findings reveal that the hamlet head acts as a mobilizer, facilitator, and mediator in fostering harmonious social interactions through social communication, consensus-based deliberation, and the reinforcement of mutual cooperation and socio-cultural traditions. Participatory and communicative leadership strengthens associative social relationships and enhances social solidarity and social capital within the community. The study concludes that the role of the hamlet head is essential in sustaining social interaction dynamics and social solidarity in Dusun VI Patumbak.